Analysis of the Impact of Neoadjuvant Chemotherapy on CD8+ Tumour Infil-trating Lymphocytes in Epithelial Ovarian Cancer - Thangam; M, Vincy T; P, Lakshmipiriya; Anand, Venu (Universitas Brawijaya, 2025)
Background: In India, ovarian cancer is one of the most common malignancies, second only to cervical cancer 1. About ninety percent of malignant ovarian cancers are epithelial ovarian carcinomas. Effective treatment modalities for advanced stage disease are still under research. Management of such advanced cancers is becoming more challenging due to therapeutic limitations. All these factors contribute to the current high mortality rate 2. Several immune markers have been postulated to affect the prognosis of the disease. This study has been undertaken to evaluate the effect of neoadjuvant chemotherapy (NACT) on Tumour Infiltrating Lymphocytes (TILs) in epithelial ovarian cancer. Aim: Evaluation of the impact of neoadjuvant chemotherapy on CD8+ TILs in epithelial ovarian cancer. Objectives: To analyze the percentage of CD8+ TILs expression in epithelial ovarian cancer. Also, to assess the effect of neoadjuvant chemotherapy on TILs. Results: 52 cases of epithelial ovarian cancers diagnosed during the period between January 2021 to June 2022 in Government Kilpauk medical college and its annexe Government Royapettah hospital, India were included in the study.. Representative tissue sections were taken from specimens sent for histopathological examination .TILs was evaluated using CD8 Immunohistochemistry. High density of CD8+ TILs (>=20/HPF) was seen in 42.3% of cases. Patients who had received NACT prior to surgery showed high density of CD8 + TILs when compared to patients with no prior NACT. The association between NACT and CD 8+ TILs was statistically significant. Conclusion: The present study indicated that NACT had a positive effect on tumor immune microenvironment.